13 Using a new classification system of posttraumatic ankle instability to quantify levels of neuromuscular and perceived function. (12th October 2015) - Terada, M; Bowker, S; Hiller, CE; Thomas, AC; Pietrosimone, B; Gribble, PA
Abstract : Background: Separating chronic ankle instability (CAI) into subgroups based on the major clinical symptoms of CAI, including perceived ankle instability (PI), repeated episodes of "giving-way", and recurrent ankle sprains (RAS), may create more homogenous subgroups of participants with CAI and could help to identify mechanical, neuromuscular, and psychological characteristics in individuals with CAI. Objective: To determine if selected sensorimotor, mechanical, and self-reported measures are different among PAI subgroups healthy control participants, and PAI-copers. Design: Single-blinded, case-control. Setting: Research laboratory. Participants: Ninety-three participants (40M, 53F; age = 21.81 ± 3.63 years; BMI = 24.94 ± 4.26 kg/m 2 ) volunteered and were categorised into PI in combination with RAS (PI-RAS; n = 25), PI alone (n = 13), RAS alone (n = 12), PAI-copers (n = 18), and controls (n = 25). Interventions: Participants completed self-assessed global, regional, and psychological health-related questionnaires and assessments of neuromuscular and mechanical joint stability. Main outcome measurements: Neuromuscular outcomes included spinal reflex excitability of the soleus muscle (Hmax :Mmax ratio) and static postural control assessed with the mean of time-to-boundary minima in the anterior-posterior (TTB-AP) and medial-lateral directions (TTB-ML). For mechanical outcome measures, ankle joint laxity was measured using an ankle arthrometer. Self-reported outcomes included the Foot and Ankle Ability Measure Activities of Daily Living (FAAM-ADL), the FAAM-Sports, the Tampa Scale of Kinesiophobia-17, and Physical and Mental Summary Components of the Short-Form 36. A backward, stepwise, multinomial logistic regression was used to determine the most influential factors to classify group membership. Cohen's d effect sizes were calculated to determine the magnitude of difference in the most influential factors between groups. Results: Five outcome measures (Hmax :Mmax ratio, TTB-AP, TTB-ML, FAAM-ADL, FAAM-Sports) were the best set of indicators of group membership (χ 2 (20) = 128.67, p < 0.001). Participants with PI-RAS demonstrated the greatest neuromuscular and perceived dysfunction. Conclusions: The combination of PI and RAS appears to lead to greater degree of neuromuscular and perceived dysfunction compared to CAI-copers and healthy controls.